TOXIC AND IMMUNE ALLERGIC RESPONSES OF ANT VENOM TOXINS: A REVIEW - SHARMA, SIMRAN; UPADHYAY!, RAVI KANT (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Present review article explains ant venom components and its allergic and biological effects in man and animals. Red ants or small fire ants secrete and inject venom very swiftly to defend their nest against predators, microbial pathogens, and competitors and to hunt the prey. Ant venom is a mixture of various organic compounds, including peptides, enzymes, and polypeptide toxins. It is highly toxic, allergic, invasive and venomous. It imposes sever paralytic, cytolytic, haemolytic, allergenic, pro-inflammatory, insecticidal, antimicrobial, and pain-producing pharmacologic activities after infliction. Victims show red ring-shaped allergic sign with regional swelling marked with intense pain. Ant venom also contains several hydrolases, oxidoreductases, proteases, Kunitz-like polypeptides, and inhibitor cysteine knot (ICK)-like (knottin) neurotoxins and insect defensins. Ant venom toxins/proteins generate allergic immune responses and employ eosinophils and produce Th2 cytokines, response. These compounds from ant venom could be used as a potential source of new anticonvulsants molecules. Ant venoms contain many small, linear peptides, an untapped source of bioactive peptide toxins. The remarkable insecticidal activity of ant venom could be used as a promising source of additional bio-insecticides and therapeutic agents.